Peptide functionalized nanomaterial (metal nanoparticles) for biosensor development - Liu, Xiaohu (2015)
Biosensors development as a multidisciplinary science has been attracting researchers in many ways such as testing novel strategies, understanding new interactions and realizing potential applications. This thesis describes simple nanoparticle-based assays for detections of critical targets in a robust peptide-based manner. Potential improvement of sensitivity has been discussed in both peptide receptor side and nanoparticle transducer side. As a selected target, botulinum neurotoxin is one of the most dangerous toxins on the earth. The light chain of this toxin is a protease. Several assays for the light chain protease were then developed based on peptide-gold nanoparticle conjugates achieving different total assay time and limit of detection. In the first colorimetric mixing assay, two varied bio-functionalized particles were prepared. One was capped by novel designed biotinylated peptide substrates for botulinum neurotoxin, while the other was coated by neutravidin proteins. Immediate aggregation occurred after mixing them unless the biotinylated peptide substrates were pre-cleaved by the protease. A second way of detection, bridging assay utilized bi-biotinylated peptide substrates that caused the aggregation of neutravidin-particles. In the presence of light chain protease however the peptides were cleaved into halves resulting in no aggregation. Besides the colorimetric assays, fluorescence quenching assay was also developed using the same design of biotinylated peptide substrate-nanoparticle conjugates. With the help of a labeled streptavidin, the fluorescence was quenched by gold nanoparticles. Once the peptides were cleaved by protease, the fluorescence was recovered. Similarly a colorimetric assay was developed for human cardiac troponin I which is a critical biomarker of heart diseases. The peptide binder was adopted and redesigned for functionalizing gold nanoparticles. Due to the multivalent binding of peptides to troponin I, the peptide binder-nanoparticle conjugates aggregated soon after the addition of trace amount of targets. Improvement of sensitivity of biosensors is always favored but challenging especially when we are focusing on developing simple and robust sensors. On the receptor side, peptide binders are promising candidates of replacing antibodies with a higher robustness. They can be designed starting with peptide scaffolds and small ligands that specifically binding to targets. With fine tuning of the linker molecules in between, the final selected peptide binder will have a boosted binding affinity which will eventually improve the sensitivity of derived biosensors. Towards the same target of botulinum neurotoxin light chain, peptide binder scaffolds were proposed and synthesized. Similar ligand molecules were added to the scaffold including linkers resulting in various peptide binders for the toxin light chain. Unfortunately none of the products tested gave an acceptable binding affinity. Further effort must be done before concluding that it did not work. For instance, the peptide scaffold can be elongated as well as the linkers. On the transducer side, it is important to realize that the current colorimetric assays employing plasmonic concept is actually designed for use in combination with sophisticated equipment. In a real colorimetric assay for direct human eye detection the color change should take over rather than the peak shift. Gold-silver alloy nanoparticles were shown to be more suitable than pure gold nanoparticles by comparing their color changes. It is believed as well for a simple colorimetric assay the sensitivity will be improved when employing those alloy nanoparticles.